2016
DOI: 10.1016/j.elstat.2016.04.002
|View full text |Cite
|
Sign up to set email alerts
|

Heterogeneity of surface potential in contact electrification under ambient conditions: A comparison of pre- and post-contact states

Abstract: We measured the pattern of charging by contact electrification, following contact between a polydimethylsiloxane (PDMS) stamp and a glass substrate with gold electrodes. We used scanning Kelvin probe microscopy to map the surface potential at the same regions before and after contact, allowing a point-by-point comparison. After contact, the mean surface potential of the glass shifted by 360 mV and micron-scale heterogeneity appeared with a magnitude of ~100 mV. The gold electrodes showed charge transfer but no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
8
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 37 publications
3
8
0
Order By: Relevance
“…However, when the AFR and PTFE surfaces were brought in contact for 10 sec, there was a significant shift in the surface potential for the AFR samples from 1.187 V to 1.206 V. However, any further cycling or contacting/rubbing of the AFR and PTFE surface did not affect the surface potential of the AFR visibly, and it remained centred around the 1.206 V value. This trend of the upshift in the surface potential of the tribo-positive material is in line with that observed by Baytekin et al and Barnes et al [53,54]. However, their use of soft, high tack PDMS ensures higher conformity of the tribo-surfaces leading to a significantly higher difference in the observed surface potentials (up to 100 mV) [53,54].…”
Section: Nanoscale Insight Into Performance Of Afr/ptfe Tengssupporting
confidence: 89%
See 1 more Smart Citation
“…However, when the AFR and PTFE surfaces were brought in contact for 10 sec, there was a significant shift in the surface potential for the AFR samples from 1.187 V to 1.206 V. However, any further cycling or contacting/rubbing of the AFR and PTFE surface did not affect the surface potential of the AFR visibly, and it remained centred around the 1.206 V value. This trend of the upshift in the surface potential of the tribo-positive material is in line with that observed by Baytekin et al and Barnes et al [53,54]. However, their use of soft, high tack PDMS ensures higher conformity of the tribo-surfaces leading to a significantly higher difference in the observed surface potentials (up to 100 mV) [53,54].…”
Section: Nanoscale Insight Into Performance Of Afr/ptfe Tengssupporting
confidence: 89%
“…This trend of the upshift in the surface potential of the tribo-positive material is in line with that observed by Baytekin et al and Barnes et al [53,54]. However, their use of soft, high tack PDMS ensures higher conformity of the tribo-surfaces leading to a significantly higher difference in the observed surface potentials (up to 100 mV) [53,54].…”
Section: Nanoscale Insight Into Performance Of Afr/ptfe Tengssupporting
confidence: 89%
“…100 mV higher than that without electrification and showed more positive values after repeated contact electrification (Figure S1). The surface charge density (σ) on Au by contact electrification can be calculated using the simple capacitor model: 19 V h where ε 0 is the vacuum permittivity (8.854 × 10 −12 F/m), ΔV CPD (100 mV) is the V CPD change of Au before and after PDMS contact, and h is the lift height (10 nm) between a tip and Au film during KPFM measurement. In the results, σ is 8.8 nC/cm 2 on Au by contact electrification and shows similar levels with previously reported values in air.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Another interesting but perplexing question is how electrostatic charge becomes distributed on surfaces. It has long been known that charged surfaces are not uniformly charged, but rather have significant spatial heterogeneity in the magnitude of charge, and often even the polarity of the charge. More recently, it has been shown that these charge distributions occur with micrometer-scale positive and negative regions existing side by side. In fact, complex micrometer-scale “charge mosaics” are found to form on insulator surfaces. …”
Section: Introductionmentioning
confidence: 99%